PENCEGAHAN DBD PADA MASYARAKAT DAYAK DIWILAYAH KELURAHAN PAMPANG SAMARINDA KALIMANTAN TIMUR - Badar Badar; Lukman Nulhakim; Rasmun Rasmun (Husada Mahakam, 2021)
Abstract Introduction: Various cultures in East Kalimantan, one of which is the Dayak Kenyah ethnic culture inhabiting the Pampang Cultural Village. Purpose: This study analyzes the prevention of DHF in Pampang Samarinda Utara Village in 2020. Methods: Using a qualitative design with an ethnographic approach, sources of information from 5 main informants, 1 key informant, 1 supporting informant, Milles and Huberman models are used in data analysis with the Opencode 4.03 application. Results: Informants' knowledge about dengue fever is a new disease. The attitude of the informants still holds the culture in their daily life. Informants still depends on nature. Informants' DHF prevention measures, performing dance ceremonies (Mentiang), are still largely dependent on natural products which are used as a source of medicines (Taban). Conclusion: In general, the informants referred to DHF as "Uda-uda bala, Dadem daha bulu, Mayong meko", ate leaves (Tung kayu), such as "Bekai" leaves (natural food flavoring). Suggestion: Pampang Cultural Village to support the ethnic Dayak Kenyah culture, Sei Siring Health Center to conduct regular health education. And researchers who are interested in continuing this research should examine the content of the leaves of "Bekai" Keywords: Behavior, Prevention of DHF, Dayak Kenyah Culture Pampang Samarinda, East Kalimantan. Abstrak Pendahuluan: Beragam budaya di Kalimantan Timur, salah satunya budaya ethnic Dayak Kenyah mendiami Kelurahan Budaya Pampang. Tujuan: penelitian ini menganalisis pencegahan DBD di Kelurahan Pampang Samarinda Utara Tahun 2020. Metode: Menggunakan rancangan kualitatif dengan pendekatan etnografi, sumber informasi dari 5 orang informan utama, 1 orang informan kunci, 1 orang informan pendukung, Model Milles dan Huberman digunakan dalam analisa data dengan aplikasi Opencode 4.03. Hasil: Pengetahuan Informan tentang Demam berdarah merupakan penyakit baru. Sikap Informan masih memegang kebudayaan dalam kehidupan sehari-hari. Kepercayaan Informan masih bergantung dengan alam. Tindakan pencegahan DBD Informan, melakukan upacara tari-tarian (Mentiang), sebagian besar masih tergantung pada hasil alam yang dijadikan sebagai sumber obat-obatan (Taban). Kesimpulan: Umumnya Informan menyebut DBD dengan â€œUda-uda bala, dadem dahak bulu, mayong mekoâ€, mengonsumsi dedaunan pohon (Tung kayu),.seperti daun â€œBekaiâ€ (Penyedap rasa makanan alami). Suggestion: Kelurahan Budaya Pampang agar mendukung kebudayaan Ethnik Dayak Kenyah, Puskesmas Sei Siring agar melakukan edukasi kesehatan secara regular. Dan peneliti yang tertarik melanjutkan penelitian ini agar meneliti kandungan daun â€œBekaiâ€